Kegiatan Kunjungan Kasus Osteoarthritis Dengan Hipertensi Pada Tn. S Dengan Pendekatan Kedokteran Keluarga - Pujian, Andhini Rajo; Wirawan, Gede Dhananjaya Putra; Lestari, Dewi Indah (Universitas Pahlawan Tuanku Tambusai, 2024)
Osteoarthritis (OA) is a degenerative joint disease associated with joint cartilage damage and can cause disability in the long term. As many as 303 million people worldwide have osteoarthritis. About 11.5% more Indonesians suffer from osteoarthritis. According to Riskesdas of Banten Province in 2018, it is known that the high prevalence of joint disease in the age group over 15 years is 6.15%. Hypertension is an increase in blood pressure either systolic or diastolic. WHO notes that 1.28 billion people worldwide suffer from hypertension. Hypertension can cause vascular, cerebrovascular, kidney disease, and even death. Relieve symptoms and prevent complications of osteoarthritis in a male patient with hypertension. Mr. S, 62 years old, came to the Cikupa Health Center with complaints of increasing right knee pain. Mr. S complained of stiffness in his right leg, especially when he woke up. A holistic and comprehensive intervention result and pharmacological and non-pharmacological management for about 4 weeks showed results, patients understood about osteoarthritis and hypertension, and relieves pain in patient. The family medicine approach has been able to reduce pain symptoms in Mr. S even though the disease of osteoarthritis in Mr. S has not been resolved, and the patient already knows the types of daily and work activities to avoid reducing disease progression. By carrying out the interventions that have been given, complaints of pain in the right knee and stiffness in the right leg can be improved, and can carry out work and daily activities without obstacles.